IRK(1–3) and GIRK(1–4) Inwardly Rectifying K(+)Channel mRNAs Are Differentially Expressed in the Adult Rat Brain - Karschin, Christine (J Neurosci, 1996)
Molecular cloning together with functional characterization has shown that the newly identified family of inwardly rectifying K(+) channels consists of several closely related members encoded by separate genes. In this report we demonstrate the differential mRNA expression and detailed cellular localization in the adult rat brain of seven members of the IRK and GIRK subfamilies. Using both radiolabeled cRNA riboprobes and specific oligonucleotide probes directed to nonconserved regions of both known and newly isolated rat brain cDNAs, in situ hybridization revealed wide distribution with partly overlapping expression of the mRNAs of IRK1–3 and GIRK1–4. Except for the low levels of GIRK4 transcripts observed, the overall distribution patterns of the other GIRK subunits were rather similar, with high levels of expression in the olfactory bulb, hippocampus, cortex, thalamus, and cerebellum. Marked differences in expression levels existed only in some thalamic, brainstem, and midbrain nuclei, e.g., the substantia nigra, superior colliculus, or inferior olive. In contrast, IRK subunits were expressed more differentially: all mRNAs were abundant in dentate gyrus, olfactory bulb, caudate putamen, and piriform cortex. IRK1 and IRK3 were restricted to these regions, but they were absent from most parts of the thalamus, cerebellum, and brainstem, where IRK2 was expressed predominantly. Because channel subunits may assemble as heteromultimers, additional functional characterization based on overlapping expression patterns may help to decipher the native K(+) channels in neurons and glial cells.